On-Demand Isolation of Bacteriophages Against Drug-Resistant Bacteria for Personalized Phage Therapy - Mattila, Sari; Ruotsalainen, Pilvi; Jalasvuori, Matti (Frontiers in Microbiology, 2015)
Bacteriophages are bacterial viruses, capable of killing even multi-drug resistant bacterial cells. For this reason, therapeutic use of phages is considered as a possible alternative to conventional antibiotics. However, phages are very host specific in comparison to wide-spectrum antibiotics and thus preparation of phage-cocktails beforehand against pathogens can be difficult. In this study, we evaluate whether it may be possible to isolate phages on-demand from environmental reservoir. We attempted to enrich infectious bacteriophages from sewage against nosocomial drug-resistant bacterial strains of different medically important species in order to evaluate the probability of discovering novel therapeutic phages. Stability and host-range were determined for the acquired phages. Our results suggest that on-demand isolation of phages is possible against Pseudomonas aeruginosa, Salmonella and extended spectrum beta-lactamase (ESBL) Escherichia coli and Klebsiella pneumoniae. The probability of finding suitable phages was less than 40% against vancomycin resistant Enterococcus (VRE) and Acinetobacter baumannii strains. Furthermore, isolation of new phages against methicillin resistant Staphylococcus aureus (MRSA) strains was found to be very difficult.